Positron emission tomography (pet) radiotracers for imaging macrophage colony-stimulating factor 1 receptor (csf1r) in neuroinflammation - DANNALS Robert F; POMPER Martin G; HORTI Andrew G; NAIK Ravi (2024)
Positron emission tomography (PET) radiotracers for imaging macrophage colony stimulating factor-1 receptors in a subject afflicted with or suspected of being afflicted with a neuroinflammatory or neurodegenerative disease or disorder are disclosed.